Metal-free graphitic carbon nitride nanosheet for dual mode fluorescence and electrochemical detection of para-nitrophenol - Singh A.K.; Singh A.; Patel M.; Singh V.P.; Rosy N. (My University, 2025)
para-Nitrophenol (p-NP) contamination poses significant risks to both environmental and human health, highlighting the urgent need for sensitive and selective methods for its detection. In this study, a graphitic carbon nitride sheet (g-CNS) synthesized via a one-step hydrothermal method is proposed as a bi-functional probe for p-NP sensing. The fluorescence activity of the g-CNS was first optimized, and its quenching on the addition of p-NP was used for the fluorometric detection of p-NP. A broad linear response to p-NP concentrations ranging from 1 to 100 μM was observed, with a detection limit of 36.76 nM. The sensor exhibited excellent performance in the presence of potential interferences and was successfully applied to real sample analysis. To enhance on-site detection applicability, a g-CNS modified voltammetric sensor was developed. The g-CNS was electrodeposited on a glassy carbon electrode (GCE) using cyclic voltammetry and characterized using a range of techniques to confirm the successful modification. When applied to p-NP detection, the modified GCE demonstrated high sensitivity, with a limit of detection (LOD) of 218 nM. Furthermore, the stability, reusability, and reproducibility of the modified electrode were thoroughly evaluated, confirming its reliability for long-term use in electrochemical sensing applications. © 2025 The Royal Society of Chemistry.